House of koi - Li, Lilian (New Degree Press, 2019)
House of Koi is about identity and learning that, sometimes, your future is waiting for you in your past. The story follows Mila as she strives to reconcile the person she became in an effort to fit into her American international school with the young girl she was; the girl who spoke Mandarin and Malay with ease. Is it too late to embrace both parts of herself? When Mila is sent to the top of the mountain to live with her grandmother for a year when her parents go away for business, she cannot avoid her native tongue, even if she does try. To make matters worse, Mila must now attend a local private school, and navigate a world she seems to barely understand. Everyone keeps telling her that she should not forget her heritage, but this only takes her deeper inside herself. That is until she meets the "Fish Boy" from the bottom of the mountain. Together, they teach one another what the other is best at. However, every time Mila asks about the past, he refuses to answer. She resolves to find out what happened that caused her to be unable to look her grandmother squarely in the eye.